2017
DOI: 10.3892/ol.2017.5833
|View full text |Cite
|
Sign up to set email alerts
|

Imaging characteristics and surgical treatment of invasive meningioma

Abstract: In order to provide an effective way to prevent or substantially delay the recurrence of invasive meningioma, and improve the curative effect of surgical treatment, we collected and analyzed the clinical manifestations, pathological features, preoperative imaging characteristics as well the data obtained during the surgical treatment of invasive meningioma. From February 2014 to February 2016, 59 patients with invasive meningioma were enrolled in this study. Invasive meningioma was confirmed in all patients by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(17 reference statements)
0
7
0
2
Order By: Relevance
“…2 , 1121 However, no imaging finding was found to predict reliably the histological grade for meningioma. 5 , 6 , 19 To our knowledge, this is the largest case series examining imaging findings of brain-invasive meningiomas, which included 60 such cases. Two previous studies which examined meningioma brain invasion found a positive association with peritumoral oedema, similar to our result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 , 1121 However, no imaging finding was found to predict reliably the histological grade for meningioma. 5 , 6 , 19 To our knowledge, this is the largest case series examining imaging findings of brain-invasive meningiomas, which included 60 such cases. Two previous studies which examined meningioma brain invasion found a positive association with peritumoral oedema, similar to our result.…”
Section: Discussionmentioning
confidence: 99%
“…4 The identification of atypical meningiomas would be useful for determining prognosis, surgical planning and post-treatment follow-up. Although previous studies have discussed magnetic resonance imaging (MRI) techniques to differentiate typical from atypical meningiomas, most of them referred to the former 2007 WHO classification for histological diagnosis, 5 , 6 which did not include brain invasion as a histological criterion. Only a few studies specifically assessed imaging findings of brain-invasive and non-invasive meningiomas.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous enhancement could be due to the existence of necrosis and cystic degeneration. On account of the rapid proliferation rate, the central area of the tumor often has insufficient blood circulation, resulting in ischemic necrosis or cystic degeneration ( 25 ). The necrotic area is usually larger in more invasive tumors ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…On account of the rapid proliferation rate, the central area of the tumor often has insufficient blood circulation, resulting in ischemic necrosis or cystic degeneration ( 25 ). The necrotic area is usually larger in more invasive tumors ( 25 ). In the study, bone destructive absorption accounts for 36.4% of the bone changes in the skull base, which is much higher than that reported in the literature ( 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The surgical aim is symptom remission and if it is the case to leave the smallest cortical layer of tumour to prevent neurological alteration, even though this means subtotal resection -Simpson IV [12,19]. On the one hand this approach is preferable because of the slow growth pattern of the lesion and because gross resection is associated with increased morbidity for the infiltrative borders type, on the other hand some studies found that Simpson resection grade is a predictor factor for recurrence.…”
Section: Discussionmentioning
confidence: 99%